Ecthyma Gangrenosum: Escherichia coli or Pseudomonas aeruginosa? - Abbas, Mohamed; Emonet, Stéphane; Köhler, Thilo; Renzi, Gesuele; van Delden, Christian; Schrenzel, Jacques; Hirschel, Bernard (Frontiers in Microbiology, 2017)
Background Ecthyma gangrenosum (EG) was first described as necrotic lesions that developed in the context of Pseudomonas aeruginosa bacteremia. Many reports describe EG in the setting of non-Pseudomonal infections. In a patient with EG, initial blood cultures showed Escherichia coli, and almost occulted Pseudomonas aeruginosa bacteremia. Based on the clinical picture we suspected preponderant P. aeruginosa bacteremia, outgrown by concomitant low-grade E. coli bacteremia in the blood culture vials. Methods We performed quantitative polymerase chain reaction (PCR) assays with specific primers for P. aeruginosa and E. coli on blood collected at the same time for blood cultures. We also performed quantitative cultures of the strains isolated from the patient’s blood. Results Quantitative PCR showed that there were 1.5 x 10E7 copies/milliliter (ml) of P. aeruginosa DNA, whereas the quantity of E. coli DNA was below the detection limit of 2 x 10E4 copies/ml. We estimated that there was at least 1000 times more P. aeruginosa than E. coli. Quantitative cultures showed that E. coli grew faster than P. aeruginosa. Conclusions Our patient with EG had preponderant P. aeruginosa bacteremia, that was almost occulted by concomitant low-grade E. coli bacteremia. Quantitative PCR was complementary to blood cultures in the final microbiological diagnosis, and proved beneficial in establishing the etiology of EG. This may question the existence of non-Pseudomonal EG, and also shows that blood cultures results do not always reflect an “exact picture” of what happens in the patient’s blood at the time of sampling. This case illustrates the importance of communication between the clinician and the microbiology laboratory to ensure best possible results.